Ti(Pt, Pd, Au) based High Temperature Shape Memory Alloys. (2015) - Yamabe-Mitarai, Y.; Arockiakumar, R.; Wadood, A.; Suresh, K.S.; Kitashima, T.; Hara, T.; Shimojo, M.; Tasaki, W.; Takahashi, M.; Takahashi, S.; Hosoda, H.
Abstract: Rising martensitic transformation temperature is required to develop HTSMAs. Then, we have focused on the alloys consisting of Ti and precious metals such as TiPt, TiPd and TiAu due to their high martensitic transformation temperatures. To strengthen these compounds and control phase transformation temperature, third elements were partially substituted to the alloys. Some of the TiPd–base compounds indicated 100% shape recovery at temperature range between 400-450 °C. The effect of third elements on phase transformation and shape memory effects was investigated.